Computational and experimental identification of putative αTAT1 modulators: implications for nervous system function - Rybachuk, Oksana; Rayevsky, Alexey; Styhylias, Mariia; Samofalova, Dariia; Bulgakov, Elijah; Platonov, Maxym; Blume, Yaroslav; Karpov, Pavel (Frontiers in Pharmacology, 2025)
IntroductionThe project’s primary objective is to understand how enzymes responsible for post-translational modifications (PTMs) of microtubule elements influence ion channels in excitatory peripheral nervous system (PNS) cells, and to subsequently identify potential pharmacological agents that can act upon these molecular targets. Having identified HDAC6 and αTAT1 as the most relevant proteins for further study, we focused on αTAT1. αTAT1 is the sole mammalian enzyme known to acetylate microtubules, a process associated with regulating their dynamics and protecting long-lived microtubules from mechanical stress. Additionally, αTAT1 plays a role in nuclear processes such as DNA replication, cell migration, and axonal transport. Given the importance of αTAT1 in cytoskeletal homeostasis and the lack of known effectors, our research focused on this enzyme.MethodsWe designed a corresponding pharmacophore model hypothesis of ligand-dependent inhibition for αTAT1 and performed search for potential αTAT1 modulators using molecular interaction analysis and existing crystal structures. Confocal microscopy was used to assess cytoskeletal changes in a neural stem cell line following experimental treatment.ResultsThe activity of identified hits was confirmed via confocal microscopy. This allowed for further tuning of our screening models and generation of novel subsets of compounds.